Application of the CISG Before the Foreign Trade Court of Arbitration at the Serbian Chamber of Commerce—Looking Back at the Latest 100 Cases - Paviæ, Vladimir; Djordjeviæ, Milena (Journal of Law and Commerce, 2009)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US ZH-CN MN-MONG-CN <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Although former Yugoslavia had been active in the drafting process of the 1980 UN Convention on Contracts for the International Sale of Goods (CISG) and was one of the first countries to ratify the CISG,1 the subsequent application of the CISG before national courts and arbitral tribunals based in Serbia has not been monitored on a regular basis. This survey attempts to bridge a serious gap which has occurred in reporting cases on the CISG originating from Serbia.